1994
DOI: 10.1007/bf01954493
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic variation pattern of cerebral blood flow velocity and postconceptional age

Abstract: In preterm neonates, the risk for intracerebral haemorrhage is linked to immaturity of cerebral autoregulation. The preterm's 2-5/min cyclic variation pattern of cerebral blood flow velocity is thought to reflect the degree of immaturity of autoregulation--a speculation to be tested. In a cross-sectional study 15 infants (gestational age 26-40 weeks, postconceptional age (PCA) 26-42 weeks, age 1-99 days were investigated. We performed a 10 min pulsed Doppler tracing on an internal carotid artery by means of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…We analysed only patients with stable blood flow velocity patterns, but cyclic variations in CBFV [1,22] cannot be ruled out completely without longer periods of observation. Nevertheless, our results should not be influenced by such variations because cyclic variations affect systolic and diastolic blood flow velocity similarly [1] and the RI remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed only patients with stable blood flow velocity patterns, but cyclic variations in CBFV [1,22] cannot be ruled out completely without longer periods of observation. Nevertheless, our results should not be influenced by such variations because cyclic variations affect systolic and diastolic blood flow velocity similarly [1] and the RI remains unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…At the time, LFO in neonates was thought to represent an immature cerebral autoregulatory system, that was dampened with age ( 5 , 6 ). In contrast, in a cross-sectional study including 15 preterm and term neonates, LFO was found to be independent of PNA ( 11 ). In the latter study, oscillations were measured over a longer time scale (10 min) than previous studies, which also captures very LFO (approximately 0.02 Hz) ( 11 ).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, in a cross-sectional study including 15 preterm and term neonates, LFO was found to be independent of PNA ( 11 ). In the latter study, oscillations were measured over a longer time scale (10 min) than previous studies, which also captures very LFO (approximately 0.02 Hz) ( 11 ). In a longitudinal study including 10 preterm infants, the same research group found that although LFO was independent of PNA, LFO tended to be reduced in the early postnatal period ( 14 ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations